A study on the quality of amoxicillin capsule sold in non-traditional outlets in select areas of the City of Manila - Castro, Reyster G.
Medicine safety, efficacy, and quality are the most important criteria in ensuring optimal treatment from medicines. However, poor-quality medicines are still rampant. The World Health Organization (WHO) identified the issue of substandard and falsified medical products as one of the urgent health challenges. Substandard medical products are products that fail to meet either their quality standards or specifications, or both. Whereas falsified medical products are medicines that deliberately misrepresent their identity, composition, or source. In the Philippines, Amoxicillin is a highly used antibiotic. Due to its prominence in the pharmaceutical market, it is important to ensure both its quality and safety. Although Amoxicillin is a prescription drug, unlicensed establishments continue to sell Amoxicillin due to the lack of strict regulation. This study assessed the quality of Amoxicillin capsules sourced from non-traditional outlets in the selected areas of the City of Manila to identify the prevalence of substandard or falsified samples. Out of the 33 initially obtained samples, only 23 were analyzed due to HPLC equipment failure. The samples underwent visual inspection, pharmacopeial identification, assay, and uniformity of dosage unit tests. Results showed that 4.35% (1 out of 23) of the samples failed visual inspection and identification tests, suggesting potential falsification, while 56.52% (13 out of 23) were categorized as substandard. The remaining 39.13% (9 out of 23) complied with pharmacopeial specifications. These findings underscore the significance of addressing the presence of falsified and substandard Amoxicillin, particularly when sourced from non-traditional outlets since it causes significant risks to patients, potentially leading to treatment failure, increased out-of-pocket expenses, and contributing to antimicrobial resistance. Therefore stringent regulatory enforcement is necessary to ensure the safety and efficacy of medications in the market.